What do brothas do all day? - Mance, Ajuan Maria 1966- (Chronicle Books, 2023)
"A picture book with illustrated portraits of real Black men celebrating the daily lives and activities of African Americans, from visiting the barber shop to exploring outer space"--
Keywords: Junge; Beruf; Hobby; Mann; Schwarze; Alltag; USA; African American men / Juvenile fiction; Occupations / Juvenile fiction; Hommes noirs américains / Romans, nouvelles, etc. pour la jeunesse; Professions / Romans, nouvelles, etc. pour la jeunesse; Bilderbuch